Challenges in Implementing the Pesantren Endowment Fund: A Study of Presidential Regulation Number 82 Of 2021 On Operational Funding of Pesantren - Muhamad Mustaqim; Ahmad Atabik (Jurnal Hukum, 2024)
Pesantren has historically demonstrated self-autonomy in institutional management and finance. The forthcoming regulations governing pesantren funding provide several challenges for pesantren management. This study uses a descriptive qualitative method to examine the government's readiness to execute the Presidential Regulation (Perpres) on funding for the pesantren operations. The results of the study indicate that the government's readiness to execute the pesantren endowment fund involves the establishment of regulations as technical guidance and instructions for implementing the policy. The response of pesantren management to implementing the Perpres on funding for pesantren is predominantly positive. They fully support the implementation of the regulation that would allocate funding for pesantren. However, socialization and formulation of the regulation technical instructions and the legal derivatives from the pesantren-related policy are essential in executing the Perpres for the execution and implementation of pesantren endowment funds.